1993
DOI: 10.1161/01.str.24.12.1833
|View full text |Cite
|
Sign up to set email alerts
|

Stroke subtypes among Hispanics living in Guayaquil, Ecuador. Results from the Luis Vernaza Hospital Stroke Registry.

Abstract: Racial differences in stroke subtypes have been documented. Asians have a higher rate of cerebral hemorrhage than whites; however, there is little information about stroke subtypes among Hispanics. The purpose of this study was to determine the patterns of stroke subtypes in a population of Hispanics. Five hundred consecutive patients with a first stroke were included. Patients were collected from hospital wards, the emergency department, and the outpatient clinic to ensure inclusion of patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
37
1
1

Year Published

1995
1995
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 17 publications
7
37
1
1
Order By: Relevance
“…The general characteristics and distribution of all infarct subtypes were comparable to those reported in other recent hospital-based studies on stroke [13, 14, 15, 16, 17, 18, 19]or on single-stroke cohorts [27, 28, 29, 30, 31, 32, 33, 34]: territorial infarcts in 79.1%, small deep infarcts in 16.9% and a border zone territory in 4.0%. Our findings also confirmed the general male preponderance in ischemic stroke, except when infarction involved the anterior circulation in older patients.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The general characteristics and distribution of all infarct subtypes were comparable to those reported in other recent hospital-based studies on stroke [13, 14, 15, 16, 17, 18, 19]or on single-stroke cohorts [27, 28, 29, 30, 31, 32, 33, 34]: territorial infarcts in 79.1%, small deep infarcts in 16.9% and a border zone territory in 4.0%. Our findings also confirmed the general male preponderance in ischemic stroke, except when infarction involved the anterior circulation in older patients.…”
Section: Discussionsupporting
confidence: 85%
“…Early admission was the main characteristic in our patients; 85.4% of them were admitted the first day and 48.4% within the first 6 h. This point contrasts with most other registries in which patients are generally admitted later – up to the third week and sometimes beyond [11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 29, 30, 31, 32, 33, 34]. This high rate may also be explained by the severity of the infarction.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…2 Most South American studies involving stroke populations are based on single hospital data and do not provide information regarding quality of care. 3,4 Knowledge of quality of stroke care is of critical importance to establish short-term prognosis and select better therapeutic goals. Whereas in the near future stroke prevalence will steadily increase and direct medical costs will continue to rise, 5 it is likely that hospitals' financial support will be based on performance.…”
mentioning
confidence: 99%
“…[2][3][4] A recently published study has also suggested a high frequency of cerebral hemorrhage in the Ecuadoran population. 5 The causes of ICH are multiple, 6 and the frequency of the various etiologies are age dependent. In people younger than 45 years the most common cause is arteriovenous malformation 7 ; in individuals older than 70 years it is amyloid angiopathy 8 ; and in the intermediate age groups hypertension is the primary cause.…”
mentioning
confidence: 99%